PLANEJAMENTO GOVERNAMENTAL E DESENVOLVIMENTO REGIONAL: ESTUDO SOBRE O PPA 2016-2019 NO PARANÁ - Menon, Gelson (2018)
The present study evaluates the governmental planning and the regional development, based on the Plurianual Plan (PPA) 2016-2019, of the Government of the State of Paraná. The objective is to describe the process of elaboration of this PPA and analyze the content related to development in the state mesoregions, based on the economic, social and environmental dimensions. In order to do so, we sought to describe the procedures adopted by the executive and the state legislature in the preparation and processing of the PPA, in addition to the regionalized priorities. Using procedures of bibliographic consultation, documentary and interviews, a research of descriptive-analytical nature, with qualitative approach of the problem was conducted. The contents of interviews and records of public hearings were examined using the content analysis technique. The variables analyzed were the categories identified in the interviews, the demands expressed in the public hearings and the content of the PPA. The results of the research show that the PPA 2016-2019 presented a democratic advance in relation to the historical practices of governmental planning, mainly for the opportunity of dialogue provided to the population in the public hearings, in spite of the limitation of having been realized only in the three regions of greater income in the State. The study also found evidence that the content of the PPA 2016-2019 aims to contribute to the advance of the mesoregions of Paraná, using language that refers to the three pillars of development, social, economic and environmental.